Danish Farmers and Investors: An analysis of reasons and motivations for increasing cross-border agricultural activities in Central and Eastern European countries - Luljeta Hajderllari; Kostas Karantininis; Ole Bonnichsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
The purpose of this paper is to provide some evidence on the push and pull factors that motivate farmers to expand across their home countries' borders. The focus is on Danish expansion farmers and investor farmers setting up activities in Central and Eastern European countries like Slovakia, Poland, Romania and Latvia. Data from 44 mail surveys was analysed to explore the push and pull factors that contribute to farmers' level of activities outside their home country. The responses given in the mail survey are analysed using two analytical methods of frequency analysis and an ordered probit model. The results indicate that the important factors for Danish farmers to extend overseas are price and availability of land, institutional governance, network and image with regard to farming. These findings generally support the literature regarding reasons for farmers to increase their cross-border activities, except that we do not find a significant influence from the availability of cheap labour in the host countries.
Keywords: C51; D22; F23; Q12; Q17; 330; Denmark; Danish farmer; agriculture; cross-border; Central Eastern Europe